Slipping through the Cracks of a Welfare State: Children of Immigrants in Finland - Laura Ansala; Ulla Hämäläinen; Matti Sarvimäki (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We document large differences in educational attainment, criminal sentences and use of psychotropic medication between the children of immigrants and natives living in Finland. Among the offspring of immigrants from the OECD countries and the former Soviet Union, the disadvantage in education reverses and differences in criminal sentences disappear once we condition on parental income and location of residence. In contrast, large gaps remain for the children of immigrants from other regions, even conditional on background characteristics. Furthermore, the children of immigrants from all source areas are substantially less likely to use psychotropic medication than the offspring of natives despite their higher self-reported mental health problems. These results suggest that institutions designed to help disadvantaged natives do not fully reach the children of immigrants.
Keywords: I14; I21; J15; 330; children of immigrants; second-generation immigrants; education; crime; health